Occurrence and structure of extrafloral nectaries in Pterodon pubescens Benth. and Pterodon polygalaeflorus Benth - Paiva, Élder Antônio Sousa e; Morais, Helena Castanheira de; Isaias, Rosy Mary dos Santos; Rocha, Dulce Maria Sucena da; Oliveira, Paulo Eugênio (Pesquisa Agropecuaria Brasileira, 2001)
Extrafloral nectaries (EFNs) are structurally variable and widely spread among the angiosperms. The occurrence of EFNs in leaves of Pterodon polygalaeflorus Benth. And Pterodon pubescens Benth. (Fabaceae: Papilionoideae) were detected in adult specimens, at the time of production of new buds and flowers. The goals of the present study are to register the occurrence of the EFNs in P. pubescens and P. polygalaeflorus, and provide comparative data on the anatomical structures. The EFNs occur in the rachis and are located under the insertion of each petiolule. Each nectary consists of a small elevation whose apical portion is deeply invaginated, resulting in a depression (secretory pole), a common characteristic of both species. Unicellular, non-glandular trichomes occur along the rachis, being less numerous in P. polygalaeflorus while in P. pubescens they cover the EFNs. The secretory tissue consists of parenchyma cells with dense cytoplasm compactly arranged. The nectar reaches the surface of the EFNs by rupturing the thin cuticle which covers the secretory pole, since both species lack stomata or any other interruption at the epidermis. The basic difference between the two species, in relation to the EFNs, is the density of the pubescence, which is always greater in P. pubescens. Structural and dimensional modifications may be observed, even between basal and apical nectaries in the same rachis, so it does not constitute a taxonomical tool.